2020
DOI: 10.3904/kjim.2018.055
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinical risk factors and severity of dysphagia after extubation based on a videofluoroscopic swallowing study

Abstract: Background/Aims: This study aimed to evaluate the correlation between clinical risk factors of post-extubation dysphagia (PED) and the severity of impaired pharyngeal swallowing function assessed via videofluoroscopic swallowing studies (VFSSs). Methods: This study was a retrospective review of medical records. Of 116 patients who were admitted to the intensive care unit and underwent VFSS, 32 who had non-neurologic disorders and experienced prolonged intubation (for more than 48 hours) were diagnosed with PED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
(39 reference statements)
0
8
0
3
Order By: Relevance
“…In patients ventilated for more than 10 days, prevalence of dysphagia was even higher, up to 95.5%. According to literature, in non-COVID-19 patients 7,36,37 , severe dysphagia seems to be strictly correlated with MV length and ICU LOS. In our study, we reported for the first time data on dysphagia in COVID-19 patients, who seem to be burdened by a higher incidence of dysphagia already at a very early stage, when compared to other patients, as seen in the studies of Kim et al 7 , Oliveira et al 36 and Yang et al 37 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In patients ventilated for more than 10 days, prevalence of dysphagia was even higher, up to 95.5%. According to literature, in non-COVID-19 patients 7,36,37 , severe dysphagia seems to be strictly correlated with MV length and ICU LOS. In our study, we reported for the first time data on dysphagia in COVID-19 patients, who seem to be burdened by a higher incidence of dysphagia already at a very early stage, when compared to other patients, as seen in the studies of Kim et al 7 , Oliveira et al 36 and Yang et al 37 .…”
Section: Discussionmentioning
confidence: 94%
“…According to literature, in non-COVID-19 patients 7,36,37 , severe dysphagia seems to be strictly correlated with MV length and ICU LOS. In our study, we reported for the first time data on dysphagia in COVID-19 patients, who seem to be burdened by a higher incidence of dysphagia already at a very early stage, when compared to other patients, as seen in the studies of Kim et al 7 , Oliveira et al 36 and Yang et al 37 . This may be explained by the strong inflammatory response induced by SARS-CoV-2 and by its consequent systemic effects, potentially triggering a severe generalized neuromuscular impairment also involving pharyngeal muscles.…”
Section: Discussionmentioning
confidence: 94%
“…In patients ventilated for more than 10 days, prevalence of dysphagia was even higher, up to 95.5%. According to literature, in non-COVID-19 patients [ 7 , 38 , 39 ], severe dysphagia seems to be strictly correlated with MV length and ICU LOS. In our study, we reported for the first time data on dysphagia in COVID-19 patients, who seem to be burdened by a higher incidence of dysphagia already at a very early stage, when compared to other patients, as seen in the studies of Kim et al [ 7 ], Oliveira et al [ 38 ] and Yang et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, in non-COVID-19 patients [ 7 , 38 , 39 ], severe dysphagia seems to be strictly correlated with MV length and ICU LOS. In our study, we reported for the first time data on dysphagia in COVID-19 patients, who seem to be burdened by a higher incidence of dysphagia already at a very early stage, when compared to other patients, as seen in the studies of Kim et al [ 7 ], Oliveira et al [ 38 ] and Yang et al [ 39 ]. This may be explained by the strong inflammatory response induced by SARS-CoV-2 and by its consequent systemic effects, potentially triggering a severe generalized neuromuscular impairment also involving pharyngeal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…One previously underrecognized consequence of ARF is post-extubation dysphagia and subsequent aspiration [3,4]. More than 30% of ARF survivors aspirate when formally tested and many still have dysphagia at the time of hospital discharge [3][4][5][6][7][8][9][10][11][12][13][14]. Aspiration is associated with many deleterious consequences including pneumonia, percutaneous feeding tube placement, long term care facility admission, and increased mortality [3][4][5]14],…”
Section: Introductionmentioning
confidence: 99%